2015
DOI: 10.3171/2014.11.peds14347
|View full text |Cite
|
Sign up to set email alerts
|

Ventriculoperitoneal shunt perforations of the gastrointestinal tract

Abstract: OBJECT The purposes of this study were to evaluate the frequency with which children presented with ventriculoperitoneal (VP) shunt perforations of the gastrointestinal (GI) tract, to determine the type of shunts that caused the perforations, and to compare the stiffness of perforating catheters with the stiffness of catheters from other manufacturers. METHODS Medical records were reviewed of 197 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 27 publications
1
15
0
3
Order By: Relevance
“…Thiongo et al report on a case where the retrograde spread of infection led to an enterocutaneous fistula, wherein the subcutaneous abscess moved upward from the intestine to the chest [13]. Similarly, in our case, the subclavicular abscess was caused by the retrograde spread of infection.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Thiongo et al report on a case where the retrograde spread of infection led to an enterocutaneous fistula, wherein the subcutaneous abscess moved upward from the intestine to the chest [13]. Similarly, in our case, the subclavicular abscess was caused by the retrograde spread of infection.…”
Section: Discussionsupporting
confidence: 67%
“…The etiology of BPPC remains unknown in many cases. However, several risk factors have been postulated including the thin bowel wall of children, stiff distal catheters, silicone allergy, or use of abdominal trocars [13]. The mechanisms of BPPC may be categorized into the following two types: an acute-traumatic type occurring during the initial distal catheter placement or a chronic-irritative type [7].…”
Section: Discussionmentioning
confidence: 99%
“…9 Other predisposing factors include type of catheter used, one study had observed that catheter with greater friction force tends to be tangled with abdominal tissue or omentum leads to perforation of bowel. 10 The redundant length of VPS within peritoreal cavity might increase friction force with bowel thus leads to migration and perforation.…”
Section: Resultsmentioning
confidence: 99%
“…Death is reported in up to 15% of cases. Nonetheless, signs of peritonitis occur in less than 25% of patients and most of the cases are asymptomatic or exhibit catheter protrusion through the anus or mouth [3,6] . This patient denied abdominal pain and there were no radiological signs of free air in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%